O cenário internacional sob o olhar da imprensa regional : o Jornal a Federação e a Primeira Guerra Mundial - Rosa, Maria Dionéia Paula da (2017)
The purpose of this paper is to contemplate Brazil’s opinion during the First World War, through an analysis of the reports related to the event and published in A Federação newspaper that was produced in Porto Alegre from 1884 to 1937 and it was circulating through the whole state. The specific objective was to understand how the journalistic approach in the articles published by A Federação, whether written by journalists or newspaper reproductions from Rio de Janeiro and São Paulo, has been changing during the conflict, keeping always the main ideas that guided the policy adopted by Brazil for the Great War, passing through approximation and distancing moments, either with the Triple Entente countries or the Triple Alliance ones. A bibliographical and documentary research was accomplished to answer this issue. The bibliographical research counted mainly on the collection of indirect data of the most diverse scholars of the subject. The documentary research was carried out in the digital file from National Hemeroteca. As part of the effort to contextualize the Great War, images were used from moments that changed the course of Brazil's participation in the conflict, as well as the fully decrees that regulated the neutrality and the state of war. At first, we contextualize the economic, social and political structure of Brazil at the beginning of the 20th century, through diplomatic relations and internal conflicts. In a second moment the research emphasized the importance of the press and its evolution during the years of the Great War, besides the gradual change of course of Brazilian policies towards the war, we went from the neutrality to the rupture of relations with Germany. The third chapter shows the position adopted by Brazil in the last years of World War I and the country's contribution to the conflict alongside the Triple Entente and the participation of Brazilian delegation in the peace agreements. This concludes that as A Federação newspaper belongs to Rio Grandense Republican Party it contributed to its positioning that has always been in consonance with the Central Government one.